2022
DOI: 10.1111/bjd.21723
|View full text |Cite
|
Sign up to set email alerts
|

A core outcome domain set for clinical research on capillary malformations (the COSCAM project): an e-Delphi process and consensus meeting

Abstract: receives departmental independent research grants for TREAT NL registry, for which she is Chief Investigator (CI), from pharma companies since December 2019, is involved in performing clinical trials with many pharmaceutical industries that manufacture drugs used for the treatment of e.g. psoriasis and atopic dermatitis, for which financial compensation is paid to the department/hospital. Dr. Troilius is Chair of the Multidisciplinary Vascular Anomaly Group at

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…20 Implementing an online Delphi study may overcome some limitations found with decision-making processes in face-to-face committee meetings, with the advantage of less cost and feedback being provided in a controlled form. 21 It is commonly chosen as a way to achieve a consensus for clinical standards and the construction of scales. 22 This study utilized a two-round online Delphi method to formulate a behavioral assessment scale of consciousness for NHPs, incorporating the consciousness and behavior characteristics of NHPs and the clinical conscious behavior assessment scales used for patients with disorders of consciousness (DOC).…”
Section: Introductionmentioning
confidence: 99%
“…20 Implementing an online Delphi study may overcome some limitations found with decision-making processes in face-to-face committee meetings, with the advantage of less cost and feedback being provided in a controlled form. 21 It is commonly chosen as a way to achieve a consensus for clinical standards and the construction of scales. 22 This study utilized a two-round online Delphi method to formulate a behavioral assessment scale of consciousness for NHPs, incorporating the consciousness and behavior characteristics of NHPs and the clinical conscious behavior assessment scales used for patients with disorders of consciousness (DOC).…”
Section: Introductionmentioning
confidence: 99%
“…Of the challenges Langbroek et al . have faced and mastered, 2 we find three particularly interesting for other groups who aim to develop COS in dermatology. Firstly, it is widely accepted that a COS needs to address the ‘what’ (domains) and the ‘how’ (instruments) to measure.…”
mentioning
confidence: 99%
“…The Core Outcome Set (COS) for clinical research on CApillary Malformations (COSCAM) initiative has now made a substantial contribution in this issue of the BJD 2 . Following state‐of‐the‐art methods 3–5 including reviews, patient input and a formal international consensus process, 11 core outcome domains were identified.…”
mentioning
confidence: 99%
See 2 more Smart Citations